THE UNIQUE POWER OF IMPROVING THE SOCIAL PEDAGOGICAL ACTIVITY OF STUDENTS IN MULTIMEDIA VOCITAS - Rahimova Feruza Najmiddinovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the improvement of social pedagogical activities of students through multimedia tools, further development of educational activities through videos in the process of higher education.